International Economic Organizations in Retrospect: From Perpetual Peace to Regional Integration - Boundi Chraki, Fahd (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose of this article is to make a brief retrospective study of international economic organizations on the perpetual peace, the rise of mercantile capital and the consolidation of the monetary system, the institutionalization of the international relations through the gold standard system, and the process of economic integration after the Second World War. The main conclusion is that the international economic organizations, in addition to being built based on the need to maintain peace among states, have been defined by the dominant economic theories throughout the historical development of capitalism.